SIRT7 suppresses energy expenditure and thermogenesis by regulating brown adipose tissue functions in mice - Tatsuya Yoshizawa; Yoshifumi Sato; Shihab U. Sobuz; Tomoya Mizumoto; Tomonori Tsuyama; Md. Fazlul Karim; Keishi Miyata; Masayoshi Tasaki; Masaya Yamazaki; Yuichi Kariba; Norie Araki; Eiichi Araki; et al. (Nature Communications, 2022)
Sirtuins have been reported to positively regulate brown adipose tissue thermogenesis. Here the authors report that brown adipocytic SIRT7 suppresses whole-body energy expenditure and thermogenesis in mice, potentially by attenuating batokine gene expressions and Ucp1 mRNA translation.